Identification of Competencies for Green Jobs in Tourism Skills at TVET: A Systematic Literature Review - Riswano Riswano; Isma Widiaty (Journal of Vocational Education Studies, 2023)
Sustainable tourism is a concept aimed at addressing the negative impacts of the tourism industry on the environment, society, and culture. In this context, research on the identification of competencies for green jobs in the field of tourism is crucial for the development of a responsible and sustainable tourism industry. The objective of this study is to analyze the relationship between green competencies and green jobs, and to identify the competencies required for green jobs in the tourism sector. This research adopts the Systematic Literature Review (SLR) method following the PRISMA guidelines. A total of 520 articles were collected from Google Scholar, Scopus, and ScienceDirect, and after applying the predetermined criteria, 58 relevant articles were included for analysis. The findings of the study indicate that TVET plays a vital role in preparing the workforce for the transition towards sustainable tourism and there is a link between green competencies and green jobs in the tourism sector as seen from the fact that there is an increasing demand for green workers who must master green competencies, the implication is that it is important to implement green competency-based learning on TVET and this all needs support from the government, the tourism industry sector and the community.